Skip to main content
Solve for c
Tick mark Image

Share

c=\sqrt{62} c=-\sqrt{62}
Take the square root of both sides of the equation.
c^{2}-62=0
Subtract 62 from both sides.
c=\frac{0±\sqrt{0^{2}-4\left(-62\right)}}{2}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 1 for a, 0 for b, and -62 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
c=\frac{0±\sqrt{-4\left(-62\right)}}{2}
Square 0.
c=\frac{0±\sqrt{248}}{2}
Multiply -4 times -62.
c=\frac{0±2\sqrt{62}}{2}
Take the square root of 248.
c=\sqrt{62}
Now solve the equation c=\frac{0±2\sqrt{62}}{2} when ± is plus.
c=-\sqrt{62}
Now solve the equation c=\frac{0±2\sqrt{62}}{2} when ± is minus.
c=\sqrt{62} c=-\sqrt{62}
The equation is now solved.